Information systems security : 12th International Conference, ICISS 2016, Jaipur, India, December 16-20, 2016 : proceedings /: 12th International Conference, ICISS 2016, Jaipur, India, December 16-20, 2016 : proceedings. (2016) - Unknown
No abstract available